"They worried I'm dangerous? I'm absolutely harmless": US academic Steven Salaita speaks out after losing his job for posting controversial tweets. - Levinson, Nan, 1949- (Tufts University. Tisch Library., 2016)
When academic Steven Salaita was fired from a US university for outspoken comments on Twitter, he brought debates about academic freedom into the headlines. Nan Levinson interviews him about the challenges to free speech in the classroom.